Medicina rigenerativa in ortopedia e traumatologia: la stimolazione biofisica - D’Addona, A.; Izzo, A.; Ruosi, L.; Santulli, A.; Ruosi, C. (Lo Scalpello - Journal, 2019)
REGENERATIVE MEDICINE IN ORTHOPAEDICS: THE BIOPHYSICAL STIMULATION Cartilage lesions are considered to be the first cause of disability in the active population. Treating cartilage injuries is often a challenge for orthopaedic surgeons, owing to the poor regenerative potential of chondrocytes. Pulsed electromagnetic fields (PEMFs) improve cellular proliferation and migration, and ECM induction. PEMFs during or after surgery for chondral lesion have been demonstrated to be useful in inducing better repair andmigration of chondrocytes into the bioscaffolds, and to lead to improvement in patient symptoms after surgery. In this review of the literature, we collected a significative number of studies, which support using biophysical stimulation, in particular PEMFs, as first-line treatment during and after surgery to treat chondral lesion.